Distance Adult Students' Self-Management Strategies of Online Learning Discussion - Nur Shaminah binti Mustafa Kamalu; Teoh Sian Hoon (UiTM Publisher, 2013)
With distance learning getting more attention, the need for self-management strategies of learning becomes more prevalent since online learning is independent of time and place. This study was conducted to explore adult distance online students' self-management strategies of learning and the importance of computer skill and their level of self-management strategies with regard to age and gender. A quantitative method survey research design was used to carry out the research which used questionnaire as the instrument for data collecting process. Participants involved were a group of first semester distance online learning students who were full time primary school teachers. They had registered for Technology Instruction course. Findings revealed that the level of self-management strategies of learning among these adult learners was moderate. In terms of the difference in selfmanagement strategies of learning between gender and among different categories of age, the results revealed there were no significant differences. Relationship between each component of self-management and computer skill revealed that the highest correlation was between computer skill and evaluation.